ChemInform Abstract: Copper(I)‐Catalyzed Wittig Olefination Reactions of N‐Tosylhydrazones with Trifluoromethylketones. Issue 30 (29th July 2014) - Sha, Qiang; Wei, Yunyang
Abstract In reactions of ketone derived N‐tosylhydrazones only low yields are achieved.